1996
DOI: 10.1111/j.1468-2389.1996.tb00045.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluations of Tests Used for Making Selection and Promotion Decisions

Abstract: Participants (N = 212) rated the fairness, job relevance, appropriateness, and invasiveness of 16 tests that could be used to select o r promote people into production or management positions. Fairness, job relevance and appropriateness were highly correlated, and were combined to form a composite evaluation scale. Evaluations and invasiveness ratings varied among the 16 tests, with the most positive ratings given to interviews and work samples and the most negative ratings given to astrology, graphology and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
36
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 44 publications
8
36
2
Order By: Relevance
“…This explanation echoes findings in the literature about communicating utility information regarding selection procedures to managers. Contrary to earlier studies (Latham and Whyte 1994;Whyte and Latham 1997) that demonstrated that managers had less support for a valid selection procedure when they were given utility analysis information, Carson, Becker and Henderson (2000) discovered that managers had more support for utility analysis information only when it was presented in a less complex and more comprehensible manner. Similar positive results for less complex and more comprehensible information have been found in the broader literature on organizational decision making (Dutton and Ashford 1993;O'Reilly 1983) and persuasion (Petty and Cacioppo 1981).…”
Section: Main Conclusionmentioning
confidence: 58%
See 2 more Smart Citations
“…This explanation echoes findings in the literature about communicating utility information regarding selection procedures to managers. Contrary to earlier studies (Latham and Whyte 1994;Whyte and Latham 1997) that demonstrated that managers had less support for a valid selection procedure when they were given utility analysis information, Carson, Becker and Henderson (2000) discovered that managers had more support for utility analysis information only when it was presented in a less complex and more comprehensible manner. Similar positive results for less complex and more comprehensible information have been found in the broader literature on organizational decision making (Dutton and Ashford 1993;O'Reilly 1983) and persuasion (Petty and Cacioppo 1981).…”
Section: Main Conclusionmentioning
confidence: 58%
“…The results were identical to the findings heretofore presented. We also examined whether applicants' prior experience with selection procedures might play a role (see Kravitz, Stinson and Chavez 1996). Applicants' previous selection procedure experience might serve as a moderator in the sense that the information manipulation might promote fairness perceptions of a specific selection procedure only among applicants who lack experience with that specific selection procedure.…”
Section: Effect Of Information About Reliability and Validitymentioning
confidence: 99%
See 1 more Smart Citation
“…& DeShon, 1998;Kravitz, Stinson, & Chavez. 1996;Rynes & Connerly, 1993;Smither, Millsap, Stoffey, Reilly, & Pearlman.…”
Section: Predictors Of Task 16mentioning
confidence: 99%
“…However, many o f the studies cited here have been conducted using college students as "applicants" (e.g., Chan, Schmitt, Sacco. & DeShon, 1998;Kravitz. Stinson, & Chavez, 1996;Rynes & Connerly, 1993) and they have studied a limited scope of job and test types.…”
Section: Predictors Of Task 16mentioning
confidence: 99%